5. Menstrual Hygiene Practice Among Female Adolescents In Boarding School - Mariatul Kiftia; Maulina Maulina; Mira Rizkia (Jurnal Medika Veterinaria, 2020)
Menstruation is a transition process from puberty to adulthood. This is the physiological process for female adolescents. The purpose of this study is to describe the female adolescent's menstrual hygiene practice. This is descriptive analysis research. There are 42 respondents were selected by purposive sampling methods. The results of this study show that the female adolescent's practices of personal hygiene during menstruation were good (30%). And the recommendations are expected that female adolescents have to maintain their hygiene especially for genitalia or reproductive organs. And do not use the genitalia’s cleansers or deodorizers to prevent the occurrence of the diseases and the health problems of the reproductive organ.